Analysis of amplified spontaneous emission in ring-core Tm3+-doped optical fiber - Markowski, Krzysztof; Miluski, Piotr (Photonics Letters of Poland, 2023)
This paper presents the results of numerical simulations of a ring-core thulium-doped silica fiber (RC-TDF). Enhanced spontaneous emission (ASE) was generated for a fiber with 4wt.% thulium content. An analysis of the formation of the ASE spectrum parameters (λmax, FWHM, output power) as a function of fiber length is also shown. The modal map is presented as a combination of outer and inner core radii and ∆n. Full Text: PDF References Y. Huang, Q. Xu, S. Peng, C. Xu, T. Liao, "2 μm Laser generation and amplification based on dual Tm3+-doped high-Q silica microsphere using an ASE light source for pumping", Opt Laser Technol , 153, 108282 (2022). CrossRef D. Theisen-Kunde, V. Ott, R. Brinkmann, R. Keller, "Potential of a new cw 2 μm laser scalpel for laparoscopic surgery", Med Laser Appl. 22, 139 (2007). CrossRef N.P. Barnes, B.M. Walsh, D.J. Reichle, R.J. DeYoung, "Tm:fiber lasers for remote sensing", Opt Mater (Amst), 31, 1061 (2009). CrossRef S.W. Henderson, C.P. Hale, J.R. Magee, M.J. Kavaya, A.V. Huffaker, "Eye-safe coherent laser radar system at 2.1 μm using Tm,Ho:YAG lasers", Opt Lett, 16, 773 (1991). CrossRef S.D. Jackson, "Cross relaxation and energy transfer upconversion processes relevant to the functioning of 2 μm Tm3+-doped silica fibre lasers", Opt Commun. 230, 197 (2004). CrossRef J. Wu, S. Jiang, T. Luo, J. Geng, N. Peyghambarian, N.P. Barnes, "Efficient thulium-doped 2-μm germanate fiber laser", IEEE Phot Technol Lett. 18, 334 (2006). CrossRef M.J. Barber, P.C. Shardlow, P. Barua, J.K. Sahu, W.A. Clarkson, "Nested-ring doping for highly efficient 1907nm short-wavelength cladding-pumped thulium fiber lasers", Opt Lett. 45, 5542 (2020). CrossRef P. Miluski, K. Markowski, M. Kochanowicz, M. Łodziński, J. Żmojda, W.A. Pisarski, J. Pisarska, M. Kuwik, M. Leśniak, D. Dorosz, T. Ragiń, V. Askirka, J. Dorosz, "Tm3+/Ho3+ profiled co-doped core area optical fiber for emission in the range of 1.6–2.1 µm", Sci Rep. 13, 13963 (2023). CrossRef H. Ono, T. Hosokawa, K. Ichii, S. Matsuo, H. Nasu, M. Yamada, "2-LP mode few-mode fiber amplifier employing ring-core erbium-doped fiber", Opt Express, 23, 27405 (2015) CrossRef M. Kasahara, K. Saitoh, T. Sakamoto, N. Hanzawa, T. Matsui, K. Tsujikawa, F. Yamamoto, "Design of Three-Spatial-Mode Ring-Core Fiber", J. Lightwave Technol. 32, 1337 (2014). CrossRef P. Sillard, M. Bigot-Astruc, D. Boivin, H. Maerten, L. Provost, "Few-Mode Fiber for Uncoupled Mode-Division Multiplexing Transmissions", in 37th European Conference and Exposition on Optical Communications, (2011). CrossRef S. D. Jackson, S. Mossman, "Laser-induced changes on the complex refractive indices of phase-change thin film", Appl Opt. 42, 2702 (2003). CrossRef S. Unger, A. Schwuchow, J. Dellith, J. Kirchhof, "Optical properties of ytterbium/aluminium doped silica glasses", Opt Mater Express, 10, 907 (2020). CrossRef P. Honzatko, Y. Baravets, I. Kasik, O. Podrazky, "Wideband thulium–holmium-doped fiber source with combined forward and backward amplified spontaneous emission at 1600–2300 nm spectral band", Opt Lett. 39, 3650 (2014). CrossRef P. Miluski, M. Kochanowicz, J. M. Zmojda, A. Baranowska, M. Leśniak, D. Dorosz, K. Markowski, J. Dorosz, "Large mode area fibers for single-mode transmission near 2μm", Proc. SPIE 12142, (2022). CrossRef Y. Jung, Q. Kang, H. Zhou, R. Zhang, S. Chen, H. Wang, Y. Yang, X. Jin, F. P. Payne, S. Alam, D. J. Richardson, "Low-Loss 25.3 km Few-Mode Ring-Core Fiber for Mode-Division Multiplexed Transmission", J. Lightwave Technol. 35, 1363 (2017). CrossRef